2005
DOI: 10.1016/j.neuron.2005.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Parallel “Pain” Pathways Arise from Subpopulations of Primary Afferent Nociceptor

Abstract: A major unanswered question concerning "pain" circuitry is the extent to which different populations of primary afferent nociceptor engage the same or different ascending pathways. In the present study, we followed the transneuronal transport of a genetically expressed lectin tracer, wheat germ agglutinin, in Na(V)1.8-expressing nociceptors of the nonpeptide class. We found that interneurons of lamina II are at the origin of the major ascending circuits targeted by the nonpeptide nociceptors. These interneuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
218
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(228 citation statements)
references
References 34 publications
6
218
1
3
Order By: Relevance
“…We hypothesized that noxious stimulation would trigger neuronal activity and hence c-Fos expression in the BST since it receives direct (and potentially indirect) afferents from the dorsal horn of the spinal cord (Braz et al, 2005;Burstein and Giesler, 1989;Cliffer et al, 1991). Our observations confirm that these afferents carry noxious (but not innocuous) information from the periphery to the BST.…”
Section: Significance Of Noxious Stimulation-induced Neuronal Activatsupporting
confidence: 66%
See 1 more Smart Citation
“…We hypothesized that noxious stimulation would trigger neuronal activity and hence c-Fos expression in the BST since it receives direct (and potentially indirect) afferents from the dorsal horn of the spinal cord (Braz et al, 2005;Burstein and Giesler, 1989;Cliffer et al, 1991). Our observations confirm that these afferents carry noxious (but not innocuous) information from the periphery to the BST.…”
Section: Significance Of Noxious Stimulation-induced Neuronal Activatsupporting
confidence: 66%
“…Evidence for the contribution of the BST in the emotional aspect of pain is currently twofold: anatomically, the BST receives afferents from a subpopulation of glutamatergic Cfibers (IB4 positive) that terminate primarily at limbic targets (BST, globus pallidus, hypothalamus) rather than sensory-discriminative regions of the brain (lateral thalamus, somatosensory cortex) (Braz et al, 2005). Physiologically, BST lesions block pain-induced conditioned place aversion, a measure of the emotional aspect of pain in rats (Deyama et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for nociceptors, which are the neurons specialized to detect noxious stimuli. Not only do subsets of nociceptors express different repertoires of neuropeptides, receptors, and ion channels, but they also project to different laminae in the spinal cord where they engage different CNS circuits (2)(3)(4). Importantly, studies in rodents in which different nociceptor populations have been deleted revealed remarkably selective behavioral deficits (e.g., heat, mechanical, or chemical pain), demonstrating the existence of behaviorally relevant peripheral-labeled lines for different modalities of pain (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In addition, middle‐aged patients tend to report more intensive psychological impacts of their conditions and greater pain “unpleasantness” levels (Gibson & Lussier, 2012; Rustoen et al., 2005). The information carried by mouse IB4+ neurons has been shown to be conveyed to the bed nucleus of the stria terminalis, which is involved in persistent anxiety responses, and to the globus pallidus, which is involved in motor control (Braz et al., 2005). This pathway was shown to be independent of the one utilized by IB4− neurons.…”
Section: Discussionmentioning
confidence: 99%
“…IB4+ and IB4− neurons have been shown to be different subsets at the transcriptome level (Chiu et al., 2014), follow different peripheral (Zylka, Rice, & Anderson, 2005) and central (Braz, Nassar, Wood, & Basbaum, 2005) pathways, and have been suggested to be involved in the development and maintenance of different types of pain, with IB4+ neurons implicated in mechanical and chronic pain, and IB4− neurons in inflammatory and acute pain (Dirajlal, Pauers, & Stucky, 2003; Malmberg, Chen, Tonegawa, & Basbaum, 1997; Mantyh et al., 1997). …”
Section: Introductionmentioning
confidence: 99%